Interactive Power Point On Human Movement System Material; An Effort To Improve Biology Learning Outcomes At Kaima Advent Middle School - Heltiana Heltiana; Jefry Jack Mamangkey; Anatje Lihiang (Universitas Katolik Widya Karya Malang, 2023)
The world of education plays a significant role in the development of students. So, to facilitate the learning process for students is the main task of a teacher. For this reason, teachers are not only required to make the learning atmosphere comfortable and exciting. However, the teacher must also be able to improve maximum learning outcomes for students. This study aims to determine whether the application of interactive PowerPoint learning media in the classroom can help improve student's learning outcomes in class VIII on the material of the human movement system as well as research. In contrast, the object used in this research is the application of learning media using interactive PowerPoint media at Arrival Junior High School Kaima. The type of research used is classroom action research by applying two cycles of data collection obtained from observations of teacher activities and observations of student activities as well as tests before and after the action and documentation. The data analysis technique used in this study is a qualitative descriptive technique. Based on the study results, the class action that the researchers had carried out found that before the action was taken, the student's learning outcomes were 0%, or the number of students who had completed was absent. At the same time, there was an increase of 83.33% in the first cycle, and in the second cycle, again experienced an increase of 100%. This means that learning using interactive PowerPoint media is proven to help teachers improve learning outcomes in Kaima Adventist Junior High School class VIII students.